Education and New Developments 2021 2021
DOI: 10.36315/2021end057
|View full text |Cite
|
Sign up to set email alerts
|

University Students’ Struggles With Online Learning During the Covid-19 Pandemic Lockdown

Abstract: As a result of the COVID-19 pandemic that affected most countries during the year 2020, the society had to adapt rapidly to new forms of working in which the Internet has been an essential tool. And so did the higher institutions around the world, which had to move from a face-to-face classroom environment to an online one. The change from traditional learning to online learning was so unexpected that neither the instructors nor the students may have been prepared for it and could have important consequences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In an NPR article written during the pandemic (Nadworny, 2020 ), it was speculated that computer availability declined for college students. Even if students had their own laptops, the conditions necessitated by the pandemic might have led students to share devices with others in their household working remotely or attending virtual school (Chiner et al, 2021 ). Furthermore, even if the house had multiple computers, streaming video or accessing large files across multiple computers in the home can be challenging and create bandwidth issues, particularly if all devices are on the same WiFi network.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an NPR article written during the pandemic (Nadworny, 2020 ), it was speculated that computer availability declined for college students. Even if students had their own laptops, the conditions necessitated by the pandemic might have led students to share devices with others in their household working remotely or attending virtual school (Chiner et al, 2021 ). Furthermore, even if the house had multiple computers, streaming video or accessing large files across multiple computers in the home can be challenging and create bandwidth issues, particularly if all devices are on the same WiFi network.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, even if the house had multiple computers, streaming video or accessing large files across multiple computers in the home can be challenging and create bandwidth issues, particularly if all devices are on the same WiFi network. Chiner et al ( 2021 ) reported that 31.5% of students (at a Spanish university during the pandemic) always or often had a poor Internet connection during online learning experiences. This could lead to students being dropped from live class sessions or having trouble up/downloading files.…”
Section: Introductionmentioning
confidence: 99%